Role of form and design of a written text in creation of a computer game world. The case of Heroes of Might and Magic V: Tribes of the East - Bajew, Mikołaj (Replay. The Polish Journal of Game Studies, 2021)
This article is about functions of written text in video game space. It aims to show the true potential of the written text in creating a vision of game in player’s mind and in keeping him immersed. I analyzed text material from the Heroes of Might and Magic V: Tribes of the East, a turn-based strategy video game which action takes place in the fictional, colorful, fantasy world of Ashan. The written texts in mentioned video game determines the player’s perception of the other elements in the game and affects his playing experience. The following analysis of fonts, space organization of written texts and their meaning proves that point.